VALIDATION RESULT OF TEACHING MECHANICAL WAVES MATERIALS WITH ICT BASED MATERIAL INTEGRATED CTL FOR XI GRADE STUDENTS - Auvi Winandri Utami; . Asrizal; . Hidayati; Wahyuni Satria Dewi; Metta Liana (Universitas Negeri Padang, 2022)
The 21st century skills integrates life career skills, learning and innovation-4C and information, media and technology skills. The components areneeded in learning process to make learning process more effective and efficient. The 21st century learning is transforming from teacher center to student center. Student center learning can use ICT based learning material in learning process. Based on preliminary research that use of ICT based learning material were still low. Solution of this problem is to develop ICT based learning material integrated CTL to improve students thinking skills. The method that used in this research was research and development (R&D). The object of research was mechanical wave to increase students thinking skills. The data collection instrument used were validity questionnaire. The data analysis technique used was descriptive statistical analysis. The validity instrument for ICT based learning material integrated CTL to increase students thinking skills consists of five components, namely material substance, visual communication display, learning design, software utilization and CTL assessment. The validation results obtained were 87,37 which was in the very good category. From the research can be concluded that ICT based learning material integrated CTL to increase students thinking skills are valid for use in the learning process.